Mobile Banking Adoption: Development Of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) on BSI Customers in Riau Province - Mukarromah, Lukluil; Setyono, Joko (JURNAL BISNIS STRATEGI, 2024)
The rapid development of technology in the 5.0 era demands innovation to maximize the functions of technology that can be used by humans in various fields, including the banking sector, with one of its products being mobile banking. The emergence of mobile banking has shown positive impacts with numerous benefits for customers. The purpose of this research is to study important factors that can explain customers' intention and behavior in adopting mobile banking by using constructs found in the UTAUT 2 model, then adding personal innovativeness, trust, and security variables as model developments in explaining intention and behavior in adopting BSI mobile banking. The method used is quantitative, where data were collected through online questionnaires (Google Form) distributed to 360 customers who adopted BSI mobile banking services, then analyzed using structural equation modeling techniques (SEM-PLS version 3.0). The results show that the variables of price value, habit, and security have a significant positive influence on behavioral intention. Then, habit, personal innovativeness, and behavioral intention have a significant positive influence on use behavior, while effort expectancy has an influence but a significant negative effect on behavioral intention. The empirical results of this study imply that the proposed model extension has not yet been fully applied, indicating that the adoption rate still needs improvement.